2019
DOI: 10.1017/ice.2019.198
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of an antimicrobial stewardship program on high-risk pediatric patients

Abstract: Objective:To evaluate the clinical impact of an antimicrobial stewardship program (ASP) on high-risk pediatric patients.Design:Retrospective cohort study.Setting:Free-standing pediatric hospital.Patients:This study included patients who received an ASP review between March 3, 2008, and March 2, 2017, and were considered high-risk, including patients receiving care by the neonatal intensive care (NICU), hematology/oncology (H/O), or pediatric intensive care (PICU) medical teams.Methods:The ASP recommendations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…When comparing the impact of ASP in NICU versus paediatric ICU settings, NICU ASPs appear to achieve more reduction in antibiotic consumption and use of broad-spectrum/restricted agents 25. However, there are extremely few published reports of NICU ASP and recent reports from PICUs that have achieved reduced antibiotic consumption and use of broad-spectrum antibiotics 25 36 37…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the impact of ASP in NICU versus paediatric ICU settings, NICU ASPs appear to achieve more reduction in antibiotic consumption and use of broad-spectrum/restricted agents 25. However, there are extremely few published reports of NICU ASP and recent reports from PICUs that have achieved reduced antibiotic consumption and use of broad-spectrum antibiotics 25 36 37…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy and ventilator‐dependent children are frequently prescribed broad‐spectrum empiric antibiotics for illnesses 7,11,12 . Frequent and prolonged use of antibiotics is associated with emergence of antibiotic resistance in numerous patient populations, 13–15 but there is a paucity of data specific to tracheostomy and ventilator‐dependent children.…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 5 Pair-wise comparison of hospitalizations, ED visits, and antibiotic use per year between pre-MDRO and post-MDRO Tracheostomy and ventilator-dependent children are frequently prescribed broad-spectrum empiric antibiotics for illnesses. 7,11,12 Frequent and prolonged use of antibiotics is associated with emergence of antibiotic resistance in numerous patient populations, [13][14][15] but there is a paucity of data specific to tracheostomy and ventilator-dependent children. Our study found that increased antibiotic usage and episodes of hospitalization put these patients at risk of MDROs.…”
Section: T a B L E 4 Association Between Chronic Antibiotic Use Per Y...mentioning
confidence: 99%
“…Given multiple risk factors, medical providers are often hesitant to follow ASP recommendations for de‐escalation or discontinuation of antimicrobial therapy. Although there is a lack of sufficient data about the efficacy of implementation of ASP initiatives in special populations (neonates, immunocompromised), some reports show that following ASP recommendations at least did not result in poor clinical outcomes 51 …”
Section: Areas Of Pediatric Antimicrobial Stewardshipmentioning
confidence: 99%
“…Although there is a lack of sufficient data about the efficacy of implementation of ASP initiatives in special populations (neonates, immunocompromised), some reports show that following ASP recommendations at least did not result in poor clinical outcomes. 51 …”
Section: Areas Of Pediatric Antimicrobial Stewardshipmentioning
confidence: 99%